2013
DOI: 10.1073/pnas.1313839110
|View full text |Cite
|
Sign up to set email alerts
|

Oral delivery system prolongs blood circulation of docetaxel nanocapsules via lymphatic absorption

Abstract: An original oral formulation of docetaxel nanocapsules (NCs) embedded in microparticles elicited in rats a higher bioavailability compared with the i.v. administration of the commercial docetaxel solution, Taxotere. In the present study, various animal studies were designed to elucidate the absorption process of docetaxel from such a delivery system. Again, the docetaxel NC formulation elicited a marked enhanced absorption compared with oral Taxotere in minipigs, resulting in relative bioavailability and C max… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
77
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 121 publications
(82 citation statements)
references
References 23 publications
3
77
0
2
Order By: Relevance
“…Taxanes are one example of a chemotherapeutic agents limited by low bioavailabiity due to P-gp pumps [108]. In a recent study, encapsulating docetaxel in NPs resulted in increased absorption after oral administration relative to oral Taxotere in mini pigs [109]. Furthermore, the study showed that docetaxel NPs were trafficked through the lymphatic system, avoiding first-pass liver metabolism effects such as degradation by cytochrome P450 3A4 (CYP3A4).…”
Section: Applicationsmentioning
confidence: 99%
“…Taxanes are one example of a chemotherapeutic agents limited by low bioavailabiity due to P-gp pumps [108]. In a recent study, encapsulating docetaxel in NPs resulted in increased absorption after oral administration relative to oral Taxotere in mini pigs [109]. Furthermore, the study showed that docetaxel NPs were trafficked through the lymphatic system, avoiding first-pass liver metabolism effects such as degradation by cytochrome P450 3A4 (CYP3A4).…”
Section: Applicationsmentioning
confidence: 99%
“…Some authors reported that oral administration of drugs in polymeric NC offers advantages over other nanostructured systems, such as liposomes, lipid-based systems, or most micelles, because the polymeric NC are more stable in the GIT (24,25). The polymeric wall of NC may confer a higher stability to encapsulated drugs and improve the drug body exposure (area under the concentration-time curve [AUC]) and its lymphatic transport by the oral route, as previously demonstrated (26,27). Thus, an alternative pharmaceutical formulation involving polymeric NC loaded with LYC dissolved in the oily core was developed in order to reduce the contact of the active substance with the intestinal fluids to circumvent the above-mentioned set of difficulties (14,18).…”
mentioning
confidence: 98%
“…The use of C 18 unsaturated fatty acid glycerides (Labrafil 1944 CS) in the nanocapsule core may have contributed to intestinal lymphatic targeting (See section 2.3), though this effect was not explored. In another study [193] they found that docetaxel was not systemically absorbed upon oral administration of MPs-DTX-NCs (equivalent to 10 mg/kg of docetaxel) when the rats were pre-treated with cycloheximide 1.5 h before the oral administration of MPs-DTX-NCs (Figure 9), thus suggesting oral bioavailability is due to lymphatic transport.…”
Section: Recent Developments In Targeting Oral Nanoparticles To Spmentioning
confidence: 99%